1987
DOI: 10.1002/1097-0142(19871001)60:7<1661::aid-cncr2820600740>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of psychological distress, extent of disease, and performance status in patients with lung cancer

Abstract: This study examined the association between two primary covariates, extent of disease (ED) and performance status rating (PSR), and the outcome of psychological distress in patients with small cell carcinoma of the lung. Patients were studied at the time of entry onto one of three Cancer and Leukemia Group B (CALGB) protocols: 7781 (N = 165) and 8083 (N = 139) for limited disease; and 7782 (N = 151) for extensive disease. Besides ED (limited versus extensive), a four-point rating of PSR was obtained. Psycholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
3
2

Year Published

1995
1995
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(68 citation statements)
references
References 16 publications
4
59
3
2
Order By: Relevance
“…Among the medical variables, performance status was the only predictor of fighting spirit. Previous studies have suggested that performance status is one of the most important medical factors affecting psychological distress (Bukberg et al, 1984;Lansky et al, 1985;Cella et al, 1987). This study revealed that measures o1 physical impairment other than cancer site were significantly associated with fighting spirit, suggesting that performance status is among the more important medical factors affecting cancer patients' perception of stress, as opposed to the type of cancer.…”
Section: Discussionmentioning
confidence: 53%
“…Among the medical variables, performance status was the only predictor of fighting spirit. Previous studies have suggested that performance status is one of the most important medical factors affecting psychological distress (Bukberg et al, 1984;Lansky et al, 1985;Cella et al, 1987). This study revealed that measures o1 physical impairment other than cancer site were significantly associated with fighting spirit, suggesting that performance status is among the more important medical factors affecting cancer patients' perception of stress, as opposed to the type of cancer.…”
Section: Discussionmentioning
confidence: 53%
“…Distress has been defined as "a multifactorial, unpleasant experience of an emotional, psychological, social, or spiritual nature that interferes with the ability to cope with cancer, its physical symptoms, and its treatment" [1,2]. In the oncology context, distress is multifactorial, as numerous areas in a patient's life contribute to his or her experience of distress, including physical symptoms, disease severity, treatment [3,4]; physical activity level / performance status [5][6][7]; social support (for a review see [8]); and psychological factors such as optimism [9,10], coping style [11,12], and pre-morbid or current depression [13].…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with a poor performance status have a lower tolerance for the cancer treatments [13,24] and fare worse than others with the same cancer stage and disease extent [9,26].…”
Section: Introductionmentioning
confidence: 99%